MANAJEMEN USAHA DAN PEMANFAATAN MEDIA ONLINE DALAM PENINGKATAN PENJUALAN PRODUK OLAHAN KETELA UNGU PADA KELOMPOK WANITA TANI (KWT) - Kartika Hendra Titisari; Pramono Hadi; Riana Rachmawati Dewi (LPPM Universitas Bina Bangsa, 2023)
The Community Partnership Program was implemented in the Murakabi Women Farmers (KWT) group under the Gapoktan of Kenteng hamlet, Puntukrejo Village, Karanganyar Regency. As a village that produces purple cassava, mothers are creative in making products from purple cassava. The problems found include: 1. There is no legality regarding the product. 2. There is still no certification regarding the halal status of the products sold. 3. lack of knowledge about packaging. 4. lack of ability to create a business profile. 5. lack of knowledge in online marketing. 6. lack of knowledge of labeling and trademarks. The method used is by conducting training and mentoring from May to October 2023. The results of the activities include: 1. increasing partner knowledge in online management and marketing. 2. increasing the skills of trading partners in packaging. 3. increasing partner empowerment regarding product legality and certification. The implications of this service are expected to increase partners' knowledge and provide added value in business development